Too Connected to Feel Well? Student Engagement as a Moderator of Online Vigilance and Well-Being - Ratna Dyah Suryaratri; Deasyanti Deasyanti; Lussy Dwiutami Wahyuni (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The digital age has fostered the manifestation of online vigilance. Objective: Based on this, the present study seeks to analyze how online vigilance influences the psychological well-being (PWB) of Indonesian students and the influence of student engagement on the relationship between online vigilance and PWB. Methods: This study employed a sample of 504 active undergraduate students in Greater Jakarta as the primary sample population. Prior to the main data collection, instrument adaptation was conducted with 104 pilot participants to assess item clarity and preliminary psychometric properties. Three adapted instruments were used: OVS (Online Vigilance Scale), SES (Student Engagement Scale), and PWB-PERMA (Positive Emotion, Engagement, Relationships, Meaning, Accomplishment). Results: The results indicated that high online vigilance (M = 3.45, β = −0.382, p < 0.001) served as a significant negative predictor of well-being, whereas student engagement was a significant positive predictor of well-being (β = 0.493, p < 0.001). The interaction effect was not significant (β = 0.012, p = 0.118), but simple slope analysis suggested a trend whereby the negative effect of online vigilance was attenuated among students who were highly engaged. Results further indicated that online vigilance was a risk factor, whereas student engagement was a protective factor. Available online 11 October 2023. Conclusion: The protective trend pointed to the need to increase youth literacy on academic engagement to maintain well-being in the digital age.